Capsicum - An Abbreviated Compendium - Jarret, Robert L. (2019)
Pepper (Capsicum L.) is a major vegetable and spice crop worldwide. Global production of both fresh and dried fruit continues to increase steadily in terms of area harvested and yield. Various topics are addressed in this review, including recent additions to and clarification of Capsicum taxonomy, genetic resources of Capsicum, cytogenetic studies, the current status of our understanding of the mechanisms affecting the biosynthesis of capsaicinoids, the use of gene mutations to elucidate carotenoid biosynthetic pathways and their regulation, and recent advances in whole-genome sequencing and assembly.